Anatoliy Petrovich Abramov, patriarch of economic transport science - L. A. Mazo; O. F. Miroshnichenko; E. N. Efimova; G. E. Pisarevskiy (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. The article is devoted to the 100th anniversary of the birth of a major railway economist, Doctor of Economic Sciences, Professor Anatoliy Petrovich Abramov, who made a great contribution to the development of national economic science. The economists works reflect an extraordinary bright personality who left an indelible trace in the memory of those who worked with this outstanding person.Materials and methods. The article uses facts of Anatoliy Abramov biography, memories of his colleagues at the institute, and his achievements in the form of numerous scientific publications.Results. The article outlines the outstanding economist life journey, explores his contribution to the development of economic science in railway transport, reveals his multifaceted talent.Discussion and conclusion. This article is an opportunity to pay tribute to the memory of Anatoliy Abramov, famous railway economist, founder and head of a scientific school and remarkable person.